Gdnf Acts as a Germ Cell-Derived Growth Factor and Regulates the Zebrafish Germ Stem Cell Niche in Autocrine-and Paracrine-Dependent Manners - Doretto, Lucas B. [UNESP]; Butzge, Arno J. [UNESP]; Nakajima, Rafael T. [UNESP]; Martinez, Emanuel R. M. [UNESP]; Souza, Beatriz Marques de[UNESP]; Rodrigues, Maira da Silva [UNESP]; Rosa, Ivana F. [UNESP]; Ricci, Juliana M. B. [UNESP]; Tovo-Neto, Aldo [UNESP]; Costa, Daniel F. [UNESP]; Malafaia, Guilherme [UNESP]; Shao, Changwei; et al. (MDPI, 2022)
Glial cell line-derived neurotrophic factor (GDNF) and its receptor (GDNF Family Receptor α1-GFRα1) are well known to mediate spermatogonial stem cell (SSC) proliferation and survival in mammalian testes. In nonmammalian species, Gdnf and Gfrα1 orthologs have been found but their functions remain poorly investigated in the testes. Considering this background, this study aimed to understand the roles of the Gdnf-Gfrα1 signaling pathway in zebrafish testes by combining in vivo, in silico and ex vivo approaches. Our analysis showed that zebrafish exhibit two paralogs for Gndf (gdnfa and gdnfb) and its receptor, Gfrα1 (gfrα1a and gfrα1b), in accordance with a teleost-specific third round of whole genome duplication. Expression analysis further revealed that both ligands and receptors were expressed in zebrafish adult testes. Subsequently, we demonstrated that gdnfa is expressed in the germ cells, while Gfrα1a/Gfrα1b was detected in early spermatogonia (mainly in types Aund and Adiff) and Sertoli cells. Functional ex vivo analysis showed that Gdnf promoted the creation of new available niches by stimulating the proliferation of both type Aund spermatogonia and their surrounding Sertoli cells but without changing pou5f3 mRNA levels. Strikingly, Gdnf also inhibited late spermatogonial differentiation, as shown by the decrease in type B spermatogonia and down-regulation of dazl in a co-treatment with Fsh. Altogether, our data revealed that a germ cell-derived factor is involved in maintaining germ cell stemness through the creation of new available niches, supporting the development of spermatogonial cysts and inhibiting late spermatogonial differentiation in autocrine-and paracrine-dependent manners.
Keywords: Gdnf; Gfrα1; spermatogenesis; spermatogonial stem cell; zebrafish